A multi-agent system model to integrate Virtual Learning Environments and Intelligent Tutoring Systems - Giuffra, P.; Cecilia, E.; Silveira, Ricardo A. (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
Virtual learning environments (VLEs) are used in distance learning and classroom teaching as teachers and students support tools in the teaching–learning process, where teachers can provide material, activities and assessments for students. However, this process is done in the same way for all the students, regardless of their differences in performance and behavior in the environment. The purpose of this work is to develop an agent-based intelligent learning environment model inspired by intelligent tutoring to provide adaptability to distributed VLEs, using Moodle as a case study and taking into account student's performance on tasks and activities proposed by the teacher, as well as monitoring his/her study material access.
Keywords: agents; intelligent tutoring systems; multi-agent system; virtual learning environments; IJIMAI